2020
DOI: 10.3390/cancers12123723
|View full text |Cite
|
Sign up to set email alerts
|

The CCR2/MCP-1 Chemokine Pathway and Lung Adenocarcinoma

Abstract: Host anti-tumor immunity can be hindered by various mechanisms present within the tumor microenvironment, including the actions of myeloid-derived suppressor cells (MDSCs). We investigated the role of the CCR2/MCP-1 pathway in MDSC-associated tumor progression in murine lung cancer models. Phenotypic profiling revealed maximal expression of CCR2 by tumor-resident MDSCs, and MCP-1 by transplanted TC1 tumor cells, respectively. Use of CCR2-knockout (CCR2-KO) mice showed dependence of tumor growth on CCR2 signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…To break the CCL2-CCR2 interaction and inhibit monocyte recruitment to the TME, both CCR2 and CCL2 antagonists are used ( Figure 3 ). Many preclinical studies showed high efficacy of CCL2/CCR2 antagonists, e.g., in the mouse model of lung adenocarcinoma, targeting CCR2 with a small molecule inhibitor not only reduced recruitment of M2-type macrophages but also induced tumor infiltration of activated CD8 + T cells [ 116 ]. Administration of CCL2 neutralizing antibodies reduced tumor growth, inhibited angiogenesis, and macrophage infiltration in a mouse model of clear cell renal cell carcinoma [ 117 ].…”
Section: Targeting Tams For Cancer Therapymentioning
confidence: 99%
“…To break the CCL2-CCR2 interaction and inhibit monocyte recruitment to the TME, both CCR2 and CCL2 antagonists are used ( Figure 3 ). Many preclinical studies showed high efficacy of CCL2/CCR2 antagonists, e.g., in the mouse model of lung adenocarcinoma, targeting CCR2 with a small molecule inhibitor not only reduced recruitment of M2-type macrophages but also induced tumor infiltration of activated CD8 + T cells [ 116 ]. Administration of CCL2 neutralizing antibodies reduced tumor growth, inhibited angiogenesis, and macrophage infiltration in a mouse model of clear cell renal cell carcinoma [ 117 ].…”
Section: Targeting Tams For Cancer Therapymentioning
confidence: 99%
“…MCP-1 acts as an engine that drives tumor progression and therefore may serve as an effective therapeutic target. In this regard, the CCR2 blockade (i.e., the MCP-1 receptor) shows promise due to the antitumor effects it exerts (29,36,66,75). However, MCP-1 is secreted not only by tumor cells, but also by stromal cells surrounding the tumor parenchyma (81).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 also recruits Treg lymphocytes into the TME via the downregulation of TNFSF15, whereby TNFSF15 levels are inversely correlated with the degree of CD4 + CD25 + FOXP3 + Treg lymphocyte infiltration (58). In this regard, there is a reduction of CD4 + FOXP3 + Treg lymphocytes and induction of CD8 + T-lymphocyte cytotoxicity, which restricts tumor growth in a CCR2 knockout mouse lung adenocarcinoma model (75). Similarly, blocking of the MCP-1/CCR4 signaling pathway using a CCR4 antagonist inhibits tumor growth and prolongs survival time in patients with head and neck squamous cell carcinoma (HNSCC) (76).…”
Section: Mcp-1 Recruits Regulatory T Lymphocytes (Tregs) Into the Tmementioning
confidence: 99%
“…In addition, studies using CCR2-deficient mice models indicated that the receptors were involved in the development of Alzheimer’s-like pathology and obesity [ 13 ]. Furthermore, changes in CCR2 expression were noted in cardiac and pulmonary disorder models and, to some extent, in cancer models such as adenocarcinoma [ 84 , 85 ]. Blockade of CCR2 was demonstrated to be viable in treating various inflammatory diseases, experimentally and clinically [ 86 , 87 ].…”
Section: Chemokine Receptors and Their Pet Radiotracersmentioning
confidence: 99%